2019
DOI: 10.1097/jce.0000000000000360
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Intervertebral Disc Morphology and Adolescent Idiopathic Scoliosis

Abstract: Adolescent idiopathic scoliosis (AIS) is an abnormal 3-dimensional curvature of the spine that appears in youth. In progressive cases, a small curve may be augmented rapidly and leads the victim to a high-risk surgical operation. Recognition of the AIS in the early stage can help in treating it with noninvasive methods. The goal of the study was to examine the relationship between intervertebral disc morphology and AIS as an applicable index and useful method for developing the screening and recognition of AIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The observed uneven anteroposterior disc wedge might be caused by the vertebral compression during progression of the spinal deformity. Our results also show that there was a significant correlation between the IVD wedging with curve severity which are consistent with the literatures [ 17 , 18 ]. Moreover, there is an increasing trend in VB and IVD wedging when compared between the asymptomatic controls, non-severe AIS and severe-AIS groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The observed uneven anteroposterior disc wedge might be caused by the vertebral compression during progression of the spinal deformity. Our results also show that there was a significant correlation between the IVD wedging with curve severity which are consistent with the literatures [ 17 , 18 ]. Moreover, there is an increasing trend in VB and IVD wedging when compared between the asymptomatic controls, non-severe AIS and severe-AIS groups.…”
Section: Discussionsupporting
confidence: 93%
“…The significant volume loss of IVD and NP observed in severe-AIS might be explained as a consequence of the spinal deformity. Current literatures have often heterogenetic cohorts of AIS subjects for investigation and these studies only demonstrated vertebral measurements in imaging using mixed curve severity, mixed curve type or mixed gender [9,10,17,18,24]. However, there is an inhomogeneity in AIS subjects and different treatment planning should be determined and offered based on their curve magnitude in Cobb angle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation